Securing Forest Peoples’ Rights and Tackling Deforestation in the Democratic Republic of Congo : DEFORESTATION DRIVERS, LOCAL IMPACTS AND RIGHTS-BASED SOLUTIONS /: DEFORESTATION DRIVERS, LOCAL IMPACTS AND RIGHTS-BASED SOLUTIONS. (March 2016) - Kipalu, Patrick; Koné, Lassana; Bouchra, Sarah; Vig, Stéphanie, 1979-; Loyombo, Willy
No abstract available